INFLUÊNCIA DA MÁ OCLUSÃO E HÁBITOS BUCAIS NA QUALIDADE DE VIDA, SONO E FADIGA EM ADULTOS JOVENS - CUNHA, Luana Dias da (2018)
Problematic sleep and malocclusion are changes that can occur together and may have a greater impact than if they occurred alone, in physical function, in stress and in quality of life (QoL), causing fatigue in addition. Therefore, the objective of this study was to evaluate the association between malocclusion in the quality of life related to oral health and the impacts on sleep disorders and fatigue. Material and Methods: 213 young adults of both sexes with ages between 17 and 30 years old attended the Clinic School in a University Center, in São Luís, Maranhão, Brazil, participated in the study. General oral conditions were evaluated; the malocclusion was evaluated by the Dental Aesthetic Index (DAI) and the Angle Malocclusion Classification. In addition, sociodemographic instruments were applied with validated and standardized questionnaires: Economic classification; the Portuguese version of the Oral Health Impact Profile (OHIP-14) to evaluate the Quality of Life related to Oral Health; the questionnaire on the Brazilian version of the Mini Sleep, which analyzes the subjective sleep quality and the Pittsburgh Sleep Quality Index (PSQI) and the Piper Fatigue Scale Revised for fatigue measurement described. Exposure variables were compared between sleep, malocclusion and chi-square or Fisher exact test groups. A multivariate logistic regression model was constructed including the variables that presented a P value of less than 0.10 in the bivariate analysis, allowing to calculate the adjusted odds ratio (OR) association measures and respective 95% confidence intervals. The Student's T and ANOVA tests were selected for the comparative analysis of the fatigue value among the categories of the independent variables. In addition, the Pearson correlation coefficient was calculated to estimate the relationship between the fatigue scale and other continuous variables. Results: The results show that there was no significant association between malocclusion and sleep (P> 0.05), but some deleterious habits and self-perception for orthodontic treatment cause sleep disturbances (OR = 10.09), malocclusion (OR = 2.45, OR-2.33, respectively). In addition, malocclusion and fatigue did not present a positive correlation, but the comparative analysis revealed statistically significant differences only for the sealing variables (P = .045), the level of fatigue is lower among individuals with higher satisfaction with face appearance (R = -0.15, P = 0.021), and the higher the impact of oral health on QoL the level of fatigue increases (R = +0.13, P = 0.043). Conclusion: There is a positive correlation between the impact of oral health on QoL with Class I malocclusion, anterior open bite and on the level of fatigue, as well as satisfaction with the appearance of the face decreases fatigue. Social and psychological impacts are perceived due to the perceived need for orthodontic treatment as the quality of sleep is also impaired. In addition, the normal lip sealing habit suggested an increase in tension and consequently an alteration in behavioral fatigue.